Initiation and extent of skin‐to‐skin care at two Swedish neonatal intensive care units. (11th December 2012) - Blomqvist, Ylva Thernström; Ewald, Uwe; Gradin, Maria; Nyqvist, Kerstin Hedberg; Rubertsson, Christine
Abstract Aim To describe initiation and extent of parents' application of skin‐to‐skin care (SSC) with their preterm infants at two Swedish neonatal intensive care units. Methods The duration of SSC was recorded in 104 infants' medical charts during their hospital stay, and the parents answered a questionnaire. Results Both parents were involved in the practice of SSC. Three infants experienced SSC directly after birth, 34 within 1 h, 85 within 24 h and the remaining 19 at 24–78 h postbirth. SSC commenced earlier (median age of 50 min) in infants whose first SSC was with their father instead of with their mother (median age of 649 min: p < 0.001). The earlier the SSC was initiated, the longer the infant was cared for skin‐to‐skin per day during his/her hospital stay (p < 0.001). The median daily duration of SSC was 403 min. Conclusion Early initiation of SSC had positive impact on the extent of parents' application of SSC. Even though the infants in this study were cared for skin‐to‐skin to a high extent, there is a potential for extended use of SSC in this type of hospital setting for reducing separation between infants and parents.